Analytical Quality by Design Enabled HPTLC Method for Estimation of Phytoconstituents Andrographolide, Piperine and Quercetin in Nilavembu Kudineer - Bojan, Sivagami; Bandhakavi, Sailaja; Raju, Chandrasekar; Mudduluru, Niranjan Babu (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: This work outlines a sensitive, cost-effective, reliable and ecofriendly novel AQbD approach based HPTLC for the simultaneous determination of standard samples of Andrographolide (A), Piperine (P) and Quercetin (Q) and in Nilavembu Kudineer. The dependent variable retardation factor was considered as critical method response for each of the three phytomarkers whereas the independent variables, methanol %, saturation time and development distance were regarded as critical method parameters. Materials and Methods: The chromatographic separation was performed on aluminium sheets Merck TLC of silica gel 60 F 254 using a mixture of Toluene, Ethyl Acetate, Methanol, and Formic Acid (6:2:1.5:0.5) as the mobile phase. The developed plates were analysed using densitometric scanner at 254 nm. Results: The markers were suitably resolved under optimized conditions, with Rf values of 0.58, 0.78, and 0.63 for Andrographolide, Piperine, and Quercetin. The linearity was observed in the range of 100-500 ng/band for A, P, and Q with accuracy of 98.9-99.8 %, and precision of %RSD <2. This QbD-based HPTLC method developed and validated was successfully applied to quantify andrographolide, piperine and quercetin, in Nilavembu kudineer powder and liquid formulations. Conclusion: A green chemistry approach based HPTLC method was found to be cost-effective, reliable, time-efficient and for the simultaneous quantification of A, P, and Q in NK formulation.
Keywords: Analytical QbD; Andrographolide; Piperine; Quercetin; Nilaveembu Kudineer; HPTLC